The ventral pallidum and relapse in alcohol seeking - Prasad, Asheeta A. (Br J Pharmacol, 2020)
Alcohol‐use disorders are chronically relapsing conditions characterized by cycles of use, abstinence and relapse. The ventral pallidum (VP) is a key node in the neural circuits controlling relapse to alcohol seeking and a key target of pharmacotherapies for relapse prevention. There has been a significant increase in our understanding of the molecular, anatomical, pharmacological and functional properties of the ventral pallidum, laying foundations for a new understanding of its role in relapse to alcohol seeking and motivation. Here we review these advances, placing special emphasis on how advances in understanding in the cellular and circuit architectures of ventral pallidum contributes to the relapse to alcohol seeking. We show how this knowledge improves mechanistic understanding of current relapse prevention pharmacotherapies, how it may be used to tailor these against different forms of relapse and how it may help provide insights into the mental health problems frequently co‐morbid with alcohol‐use disorders.